Optimal Return Period to Encourage the Online Shopping Tendency of Potential Bangladeshi Consumers - Sarwar, Nafish; Zabeen, Mashruha; Ara, Husna (Universiti Sains Malaysia, 2013)
Return policy is a promising catalyst to attract shoppers towards online purchasing since it compensates the dilemma of not examining the products physically before ordering. Objective of this research is to estimate an approximate return period expected by the potential Bangladeshi online shoppers to get rid of the inertia to go for adopting such recent shopping channel. Feasibility of that return period was also analyzed from retailers’ point of view to determine an optimal value. An anonymous questionnaire was designed for data collection used in the survey conducted at random locations of Dhaka city during January and February, 2013 covering 120 participants aged above 20 years old, with Internet competency. The findings show that, a maximum of 30 days return period would be optimal for both consumers and retailers.